The Main Obstacles and Countermeasures of Implementing Total Quality Management in Egypt: A Case Study - Beenish Ghafar (Eduvest - Journal of Universal Studies, 2023)
Total quality management (TQM) has effectively enhanced product quality in the manufacturing business, but services are always experiencing a low quality and hard to guarantee the product. The use of TQM in the service business issue has been studied. This research explores the key challenges and implementation strategy for the whole quality management of the Egypt’s economic condition as a research subject. This paper based on qualitative method and uses several factors to describe, such as, the mission and vision, sustainable development and improvement, effective leadership, and information systems etc. The results revealed that there are multiple obstacles, procedure; mechanism must be resolved on the Egypt’s management universities. Central decision-making, no innovation and routine and administrative complexities that weaken work and performance. The TQM application needs an extraordinarily adequate budget, the administrators, workers, do not use acceptable development and improvement methods, adopting an information system on traditional methods. Overall analysis suggests that the use of TQM characteristics in higher education in Egypt still presents obvious weaknesses. However, the average value of these six factors is less than 70 percent.